SISTEM INFORMASI AKUNTANSI PERSEDIAAN OBAT-OBATAN TERKOMPUTERISASI YANG EFISIEN DAN EFEKTIF PADA PERUSAHAAN - Riskiwati, Nonis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
Medicines are the high valuable assets for the hospital because the procurement of medicines is dealing with large amount of funds. Medicine is one of the factors which supports the recovery process of hospitalâs patients. Therefore, the management of medicines supply should be efficient and effective. To support the management of medicines supply an adequate computer-based inventory accounting information system is required. Qualitative method is carried out in this. Qualitative approach descriptive analysis is the analysis technique which is used in this research since it discloses some definitions and explanation by comparing the data which has been obtained from the research to the existing theories. Based on the research of the computer-based medicine inventory accounting information system which has been implemented by the Surabaya Hajj General Hospital has not been working properly in supporting the efficiency and effectiveness on the management of medicines supply. This problem is caused by some weaknesses on the last two indicators which are the utilization of computer and the control of computer utilization in the medicine inventory accounting information system. Because of these weaknesses some improvement recommendation are set forward in order to make the management of medicines supply at Surabaya Hajj General Hospital becomes more efficient and effective.Keywords : Accounting Information System, Computerized Supplies of Medicine.